(untitled) (Canadian Medical Education Journal, 2018)
Background: Interdisciplinary teaching (IDT) is the norm in Canadian family medicine residency programs. Literature on IDT reports many academic, collaborative and organizational benefits, but little is known about family medicine residents’ own perspectives of IDT. The purpose of this study was to explore family medicine residents’ points of view on IDT in family medicine teaching units (FMTU). Methods: A mixed methods design combined interviews and self-completed online questionnaires to explore participants’ perceptions of IDT during residency. Content analysis was conducted on the qualitative data and univariate analysis statistical tests on means and proportions were conducted on the quantitative survey questions. Results: A total of 125 family medicine residents from 12 FMTU affiliated with Université Laval (Quebec City) participated in the study (11 interviews and 114 online questionnaires). Participants perceived significant benefits of IDT, including clinical knowledge, complementary perspectives and interprofessional collaboration skills. However, they believe that IDT works best when the educators adapt their teaching to the specific needs of residents in family medicine. Conclusion: These findings support those of previous IDT research and highlight the positive impacts of interdisciplinary education in family medicine residency, especially on interprofessional collaboration. IDT should remain an essential component of the family medicine curricula. _____ Contexte: L’enseignement interdisciplinaire (EID) constitue une norme dans les programmes canadiens de résidence en médecine familiale. La littérature disponible sur l’EID fait état de plusieurs bénéfices académiques, collaboratifs et organisationnels, mais elle rend peu compte des points de vue des résidents sur ce type d’enseignement. Cette étude a pour objectif d’explorer les points de vue des résidents en médecine familiale quant à l’EID offert dans les unités de médecine familiale (UMF). Méthodes: Un devis mixte a été utilisé, s’appuyant sur des entrevues semi-dirigées et des questionnaires auto-administrés en ligne. Une analyse de contenu a été effectuée pour le volet qualitatif, et des analyses univariées et bi-variées ont été réalisées pour les données obtenues dans les questionnaires auto-administrés. Résultats: Un total de 125 résidents en médecine familiale, rattachés aux 12 UMF relevant de l’Université Laval (Québec), a participé à l’étude (11 entrevues et 114 questionnaires en ligne). Les participants reconnaissent des bénéfices significatifs à l’EID, tels l’acquisition et l’approfondissement de connaissances cliniques essentielles, l’intégration de perspectives complémentaires sur les problèmes de santé, et le développement d’habiletés à la collaboration interprofessionnelle. Ils estiment toutefois que l’EID peut s’optimiser en s’adaptant davantage aux besoins spécifiques des résidents en médecine familiale. Conclusions: À l’instar des études antérieures, les résultats de cette recherche mettent en relief les impacts positifs de l’EID pendant la résidence en médecine familiale, particulièrement ceux qui sont liés à l’apprentissage de la collaboration interprofessionnelle. L’EID devrait par conséquent demeurer une caractéristique essentielle des programmes de résidence en médecine familiale.